Highly efficient compact size 0.7W broad bandwidth power amplifier - Thein, Than Tun (2013)
In this paper, we present a highly efficient compact size three stage distributed power amplifier (DPA) for high power broad bandwidth applications. The DPA is fabricated using InGaP/GaAs hetero-junction bipolar transistor (HBT) technology. The design trade-off between power, efficiency and terminal matching is discussed. Reactive termination is used at the idle port of input and output transmission lines to improve efficiency. By compromising matching, the chip size is optimized to 1.8 mm2. Output power at 1dB gain compression (P1dB) is 30.5dBm at 3.5GHz and averages output power is around 28.5dBm across the (2.5 to 6) GHz band. The associated maximum and average Power Added Efficiency (PAE) at P1dB are 43% and 33%, respectively. Average large signal gain is 7 dB across the band. Small signal simulation results agree well with the measurements results.